Awakenings: An authentic leadership development program to break the glass ceiling - Martínez Martínez, Miryam; Molina López, Manuel; Cabo, Ruth Mateos de; González Pérez, Susana; Izquierdo, Gregorio; Gabaldón, Patricia (MDPI AG, 2021)
Companies are vital agents in achieving the United Nations’ Sustainable Development Goals. One key role that businesses can play in achieving the 5th Sustainable Development Goal on gender equality is implementing training programs for their women executives so they can reach top corporate leadership positions. In this paper,we test the effectiveness of an Authentic Leadership Development (ALD) program for women executives. By interviewing 32 participants from this ALD program and building on authentic leadership theory,we find that this program lifts women participants’ self-efficacy perception,as well as their self-resolution to take control of their careers. The driver for both results is a reflective thinking process elicited during the program that leads women to abandon the stereotype of a low status role and lack of self-direction over time. Through the relational authenticity developed during the program,women participants develop leadership styles that are more congenial with their gender group,yet highly accepted by the in-group leader members,which enhances their social capital. After the program,the women participants flourished as authentic leaders,were able to activate and foster their self-esteem and social capital,and enhanced their agency in career advancement,increasing their likelihood of breaking the glass ceiling. © 2021 by the authors. Licensee MDPI,Basel,Switzerland.
Keywords: Detection method; Gender; Leadership; Sustainable development; Sustainable Development Goal; Training; Authentic leadership; Authentic leadership development program; Glass ceiling; Women executives; 63 Sociología::6309 Grupos Sociales::6309.09 Posición social de la mujer; ODS 5 - Igualdad de género; ODS 10 - Reducción de las desigualdades